3D measurement of movements of fish fins using high-speed cameras-I - Tan, John Wei You (2015)
Despite the square shape and the looks of clumsiness and bulkiness that the boxfish tends to leave an impression on others, the body shape of the boxfish is design to aid in the navigation of the fish through tight spaces. This unique phenomenon has attract and drawn attention from researcher to understand the physics behind it. This report will show the movement of the pectoral fins on the boxfish and how it is able to utilise its fins to propel itself through the water and to navigate through tight spaces efficiently despite of its bulky body structure. By the use of 2 video cameras simultaneously, a 3D analysis of the movement of fish fin is able to be completed. From the captured video frame images, the boxfish can be observed to use the fins as a way of stabilising itself in regardless of the current that is flowing towards it, this is achieved by the use of its fins to create force to counter the flow of water, thus maintaining its stable position. The findings from this report is able to generate great depth of information for engineers and designer when working on underwater vehicle that required a high amount of stability.